Training cadres and establishment of an integrated development post for non-communicable diseases based on a mosque - Eliska, Eliska; Dur, Sajaratud (Journal of Community Empowerment for Health, 2024)
Introduction: Non-communicable diseases (NCDs) are the highest cause of death due to non-communicable diseases in Indonesia. This condition is certainly very worrying, because the trend of NCDs is increasing followed by a shift in disease patterns, where previously NCDs were experienced by the elderly group, are now starting to threaten younger age groups. Public awareness of NCD risk factors needs to be increased. This requires community participation in PTM (penyakit tidak menular) integrated development activities (Posbindu). Posbindu PTM is an activity for early detection and monitoring of the main risk factors for PTM through community participation. The aim of this activity is cadre training and the establishment of a mesque-based Posbindu PTM. Methods: The method used is Asset Based Community Development (ABCD). The ABCD method is a service method that focuses on the strengths and capacities of local communities. The establishment of the PTM Posbindu was carried out at the Aisyah Abdul Latif Farah Mosque, Namorambe District, Deli Serdang Regency. There were 10 cadres recruited at Posbindu PTM Mosque. Results: The results of the establishment of the mask-based PTM Posbindu are expected to be able to detect PTM risk factors as early as possible and reduce the number of PTM congregants at mosques in particular and society in general. Conclusion: The socialization and formation of the mosque-based Posbindu PTM received positive support from the Deli Serdang Health Service and the Aisyah Abdul Latif Farah Mosque.